Competitividade dos sistemas de irrigação de arroz no Rio Grande do Sul - Chiapinoto, Fabiane Volpato (2017)
The present dissertation aims to analyze the competitiveness of rice in the natural and mechanical irrigation systems of Rio Grande do Sul. More specifically, describe the irrigation systems used in rice production; determine the competitiveness of rice production in each irrigation system; and to evaluate the effects of changes in production costs on the competitiveness of rice cultivation. The method of the Policy Analysis Matrix (PAM) is used to determine the competitiveness of the systems. This instrument uses an integrated system of accounting and economics, which analyzes income and costs at private prices and at social prices, through two accounting identities: profit, given the difference between revenue and costs; and the extent to which policy divergences or distortions and market failures. In the construction of the PAM and estimation of its indicators, the production cost of rice irrigated with semi-direct planting is used for the natural irrigation system, mechanical ─ diesel and mechanical ─ of the Instituto Rio Grandense do Arroz (IRGA), harvest 2015/16. The results per hectare show that the base system has a loss of R$ 1.168,10; the gravity irrigation system shows a loss of R$ 915,16; the diesel irrigation system has a loss of R$ 1.442,62; and, the electric irrigation system shows a loss of R$ 1.237,36. Therefore, rice production does not appear to be competitive in any of the analyzed systems, since all of them present losses. The system that is relatively more competitive, that is, that has less damage, is the of natural irrigation, followed by the electrical irrigation system and, finally, the diesel engine. In the PAM sensitivity analysis, with 10,00% increases in electric energy price and 10,00% in the price of diesel, as well as the costs of a further repression for mechanical systems, the greatest negative impact on profit occurs in the repression to diesel, followed by electric repression, diesel irrigation and electric irrigation. It should also be considered that in the calculation of fixed costs an amortization rate of 6,00% is used. This cost is rarely accounted for by the producer and is not part of the disbursement, which creates a sense of bigger profitability in the crop.